A Model For The Blending Of Coals To Meet Coal Compliance Requirements - R. S. Datta (Society for Mining, Metallurgy & Exploration, 1991)
Regulations on sulfur emissions have caused the electric utilities to evaluate various methods of meeting them. Low-sulfur, low-volatile coals can be burned alone or blended with high-volatile? coals. This option may be a cost-effective alternative to the installation of scrubbers on coal-fired combustion systems. In some blending applications, problems may be encountered because the low sulfur content and high calorific value of the low-volatile or other clean coal allow it to economically upgrade extremely poor quality coal. While this is done to meet specification purposes, actual boiler performance may be dominated by the poorer quality coal. Thus, the reputation of the low-volatile or other clean coal suffers. As a result of laboratory and full scale testing, conducted over the last five years, a model has been developed to evaluate the relative combustion characteristics of various coals and coal blends. A database for different coals has been gathered. This paper presents the model and shows how power plants and coal mine personnel can use it to evaluate their coals from different sources. It can be used to blend two or more coals from different sources so that thee blended coal has flame stability characteristics which are similar to those of the baseline coal.